Obstructive fibrinous pseudomembrane tracheitis after double-lumen tube intubation -a case report- - Jia-Hui Chua; Brenda Ling Hui Sim; Tina Koh Puay Theng; Sophia Chew (Korean Journal of Anesthesiology, 2022)
Background Obstructive fibrinous pseudomembrane tracheitis (OFPT) is a rare complication of endotracheal intubation. Case We describe the case of a 73-year-old woman who underwent short-term intubation for video-assisted thoracoscopic surgery and developed an acute life-threatening stridor two days after extubation. The patient required an emergency tracheostomy to maintain airway patency and a microscopic direct laryngoscopy procedure was performed thereafter with removal of the obstructive pseudomembrane. Subsequently, the patient also suffered a non-ST-elevation myocardial infarction. The patient successfully recovered, and the tracheostomy was subsequently decannulated two months later. Histological examination revealed mucosal ulcerations and inflammatory changes. Conclusions OFPT is an uncommon cause of life-threatening airway obstruction after extubation that is not often recognized immediately but can usually be treated with early bronchoscopic intervention or microscopic direct laryngoscopy.